2002
DOI: 10.1128/jb.184.2.344-349.2002
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Toluene ortho -Monooxygenase for Enhanced 1-Naphthol Synthesis and Chlorinated Ethene Degradation

Abstract: Trichloroethylene (TCE) is the most frequently detected groundwater contaminant, and 1-naphthol is an important chemical manufacturing intermediate. Directed evolution was used to increase the activity of toluene ortho-monooxygenase (TOM) of Burkholderia cepacia G4 for both chlorinated ethenes and naphthalene oxidation. When expressed in Escherichia coli, the variant TOM-Green degraded TCE (2.5 ؎ 0.3 versus 1.39 ؎ 0.05 nmol/min/mg of protein), 1,1-dichloroethylene, and trans-dichloroethylene more rapidly. Whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
165
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 41 publications
3
165
0
Order By: Relevance
“…The I100Q and I100C mutants indicate that the residue in this position need not be hydrophobic for TMOs to be efficient catalysts and suggest that a small side chain is not beneficial, perhaps due to limited gating ability and greater exposure to solvent. A Val to Ala mutation of the analogous gate residue in T2MO from Burkholderia capacia G4, a member of the three-component PH family, resulted in enhanced ability to degrade naphthalene and threering fused aromatics including phenanthrene, fluorene, and anthracene (48). In the light of the present structures, these findings strongly suggest that members of the PH subclass have a similar substrate channel.…”
Section: Resultsmentioning
confidence: 51%
“…The I100Q and I100C mutants indicate that the residue in this position need not be hydrophobic for TMOs to be efficient catalysts and suggest that a small side chain is not beneficial, perhaps due to limited gating ability and greater exposure to solvent. A Val to Ala mutation of the analogous gate residue in T2MO from Burkholderia capacia G4, a member of the three-component PH family, resulted in enhanced ability to degrade naphthalene and threering fused aromatics including phenanthrene, fluorene, and anthracene (48). In the light of the present structures, these findings strongly suggest that members of the PH subclass have a similar substrate channel.…”
Section: Resultsmentioning
confidence: 51%
“…First, the x-ray structure of the methane monooxygenase hydroxylase (MmoH) indicates that a short access path from solvent to the diiron center may pass through a ''Leu gate'' (27). Second, directedevolution studies of toluene 2-monooxygenase revealed that a V106A mutation in this ''gate'' region led to an increased reactivity with a larger substrate, naphthalene (28). Third, the position of G103L used in these studies is predicted to lie along this entry portal, in close proximity to the (Fe) 2 center.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins with several activities (multipurpose enzymes) may have a wide range of biotechnological applications related (but not limited) to industrial organic synthesis and metabolic engineering [12][13][14][15][16][17]. However, natural protein promiscuity (as described in the two preceding paragraphs) may perhaps be of limited use in the development of these multipurpose catalysts.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%